Strong Rashba Effect and Different f−d Hybridization Phenomena at the Surface of the Heavy‐Fermion Superconductor CeIrIn5. (3rd December 2021) - Mende, Max; Ali, Khadiza; Poelchen, Georg; Schulz, Susanne; Mandic, Vladislav; Tarasov, Artem V.; Polley, Craig; Generalov, Alexander; Fedorov, Alexander V.; Güttler, Monika; Laubschat, Clemens; Kliemt, Kristin; et al.
Abstract: New temperature scales and remarkable differences from bulk properties have increasingly placed the surfaces of strongly correlated f materials into the focus of research activities. Applying first‐principles calculations and angle‐resolved photoelectron spectroscopy measurements, a strong Rashba effect and spin‐split surface states at the CeIn surface of the heavy‐fermion superconductor CeIrIn5 are revealed. The unveiled 4 f ‐derived electron landscape is remarkably distinct for surface and bulk Ce implying the existence of novel temperature scales near the surface region in this material. These results show that ab initio calculations can reliably predict the unusual electronic and spin structure of surfaces of strongly correlated 4 f systems where Rashba spin‐orbit‐coupling phenomena emerge. It is suggested that the structural blocks of such materials can be combined with magnetically active layers for engineering of novel nanostructural objects with appropriate substrates where the diversity of f ‐driven properties can be applied for the development of novel functionalities. Abstract : The Rashba spin‐split surface state is found at the Ce‐In surface of heavy‐fermion superconductor CeIrIn5 . The surface state is unusual and reveals a heavy linear dispersion in a wide momentum range. A distinct 4 f electron landscape is unveiled for surface and bulk‐like Ce atoms. These results suggest that CeIrIn5 exhibits novel temperature scales near the surfaces.